Posture Assessment of Rubber Tappers: A Comparative Analysis of OWAS, REBA, RULA, and PERA Methods - Varghese, Abi; V Panicker, Vinay; George, Joby (La Medicina del Lavoro, 2025)
Background: The study provides a comprehensive ergonomics assessment of the postures encountered by rubber tappers using the OWAS, REBA, RULA, and PERA methods and compares the risk levels across various ergonomic assessment methodologies. Methods: The research examines the postures of fifty-one selected rubber tappers from the state of Kerala, India, during rubber tapping, analyzing 1111 different working postures. The postural assessment was conducted by analyzing video recordings of the work tasks and evaluating the postures using OWAS, REBA, RULA, and PERA. Each method’s focus and application were considered to comprehensively evaluate the postural risks. Results: The demographic characteristics indicate that the workforce mostly consists of middle-aged males involved in physically strenuous activities. The result shows that the RULA method, emphasizing upper limb postures, is particularly suited for assessing postural loads in rubber tapping, highlighting the need to match ergonomic tools to the specific demands of work activities. While OWAS provides a general overview, RULA focuses on upper limbs, REBA assesses whole-body postures, and PERA incorporates cyclic work factors, enabling targeted ergonomic interventions. Additionally, it is crucial to consider that each method OWAS, RULA, REBA, and PERA has distinct strengths and applications. Conclusions: The research highlights the need for tailored ergonomic interventions for tasks such as ’Incision on the Channel’. Ultimately, the study validates implementing a context-specific approach for assessing ergonomic parameters and intervention measures aimed at enhancing the overall occupational health of rubber tappers.